School-to-work transition: The role of life satisfaction, risk perception, and resilience in youth career decision-making - Petar Stanimirović; Tea Borozan; Katarina Petrović; Dragan Bjelica; Zorica Mitrović; Marko Mihić; Dejan Petrović; Anđelija Đorđević Tomić (PLoS ONE, 2025)
Young people often face uncertainty during the transition from education to work, along with high unemployment and job dissatisfaction, which is addressed in the EU Youth Strategy, highlighting the need for better career support. This study aimed to identify main factors influencing youth career decisions and to develop a decision-making model. Five core constructs were defined through literature review: Dealing with Uncertainty, Risk Preference, Adaptability and Resilience, Education and Support, and Life Satisfaction. Data were collected from 673 engineering students. Regression analysis was used to test the proposed model and hypotheses, while Mann-Whitney and Kruskal-Wallis tests examined group differences. The developed model accounts for 46.2% (R² = 0.462) of the variability in students’ career choices. Adaptability and resilience emerged as the most influential factor (β = 0.557). Certain differences, for specific constructs, were also observed in relation to different groups of family income, gender and extracurricular activity engagement. The model supports more informed career decisions and provides insights that may help improve career guidance and educational policy. The findings also may contribute to bridging theory and practice in career development research. The study is limited by its sample, which included only engineering students from the Republic of Serbia, potentially restricting the generalizability of the results.